Effect of the trap net emptying method on release mortality of Atlantic salmon estimated by a Bayesian system model - Ruokonen, Timo J.; Pulkkinen, Henni; Mäntyniemi, Samu; Erkinaro, Jaakko; Suuronen, Petri
2023